Effect Of Additives On The Quality Of PLA Melt Electrospun Fibers As Oil Sorbents - Mahmoud M Bubakir; Fathi Etaher Elbakoush (Surman Journal of Science and Technology, 2025)
Ultra-fine fibers of pure polylactic acid (PLA) were fabricated using melt differential electrospinning technique, to be tested as biodegradable sorbent material in oil spill cleanup situations. Three different oils were used (engine oil – crude oil – diesel oil), and the sorption capacity of the three oils were 96, 67, 53 g/g respectively, the average fiber diameter was 6.57μm, water contact angle of 138 degrees. The obtained results showed that pure PLA fibers were not a good candidate for the job, because of many reasons, such as low sorption capacity, large fiber diameter, and higher degradation rate. Sucrose fatty acid ester (SE) was used as an additive in order to improve the quality of the produced fibers, and ultra-fine fibers were made using the same technique, the effect of additive was obvious , results showed that the electrospun fibers were refined to an average diameter of 1.73μm, with sorption capacity increase of 126, 96, and 61 g/g respectively which is significantly higher than that of pure PLA, also mechanical properties of the fabricated fibers were improved , water contact angle of 135 degrees, and reduction in degradation rate was observed. Water-oil selective absorption rate of PLA/SE fiber reached almost up to 1000, and is also of big flotage and is reusable.